Success indicator for Sabah’s ecotourism sites - Tshin Lip Vui (2020)
The state of Sabah is the second largest state in Malaysia after Sarawak with which it shares its borders on its southwest region. Sabah also shares its borders with East, it is also known as Sabah, negeri di bawah bayu which mean Sabah, land Kalimantan of Indonesia in the south while the other cardinal directions face the South China Sea. The capital of the state of Sabah is Kota Kinabalu, formerly known as Jesselton during British rule. As it is located under the typhoon prone region of the Phillipines below the wind. Sabah geographical structure is a mix of mountainous regions, beaches, and tropical rainforests. The tropical rainforests of Sabah include the Kinabalu National Park which was declared as a World Heritage Site in 2000 due to its ecological diversity. Sabah is rich with many different cultures and traditions. It’s being home to about 2.9 million people with more than 30 ethnic groups. It is also known as one of the twelve mega-diversity sites in the world with its rich living heritage, ethnic makes it ideal for the ecotourism industry. Sabah enjoys a steady flow of eco-tourists from domestic and international markets with a gradual increase in the number of visitor arrival each year. Sabah’s ecotourism is categorized by its natural attraction, wildlife, and wilderness habitats. This paper sets out to interpret and develop the indicators for success ecotourism sites in Sabah and measures its’ development stage. The long-term viability of tourism can be assured only when the limitations and favorable opportunities of the overall environment for tourism development are understood and ways to measure changes induced by tourism are identified and applied. This thesis applied qualitative methods which can help researchers to understand how and why such behaviors take place. The data were then analyzed to get the results, which are success indicators of ecotourism sites based on the perception of stakeholders. There are two sets of indicators are proposed. The indicators are quite consistent with those others drawn from the literature review. The analysis also shows that there are issues that need to be addressed about these indicators. These indicators are output-based; therefore there is a need to establish the measurement or the parameters of these indicators to make it more quantifiable and more meaningful. Another aspect that the thesis identified is that the success level of each ecotourism site. The different development levels of ecotourism sites will use different strategies in their management. At the end of the thesis, the level of site development will be linked to Butler’s Model to determine the success level of the ecotourism sites. This will contribute to a tourism literature review by enhancing the knowledge of ecotourism, and to the ecotourism industry by providing a means of ecotourism success.